2009
DOI: 10.1002/rcm.3978
|View full text |Cite
|
Sign up to set email alerts
|

Mass spectrometry of nanodiamonds

Abstract: Detonation nanodiamonds (NDs) were studied by time-of-flight mass spectrometry (TOF MS). The formation of singly charged carbon clusters, C R n , with groups of clusters at n ¼ 1-35, n $160-400 and clusters with n $8000 was observed. On applying either high laser energy or ultrasound, the position and intensity of the maxima change and a new group of clusters at n $70-80 is formed. High carbon clusters consist of an even number of carbons while the percentage of odd-numbered clusters is quite low (£5-10%). On … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 42 publications
2
23
0
Order By: Relevance
“…[72][73][74][75][76][77] The (4n þ 3) clusters had higher abundance than neighboring ones ( Fig. 1(c), upper panel).…”
Section: Discussionmentioning
confidence: 93%
“…[72][73][74][75][76][77] The (4n þ 3) clusters had higher abundance than neighboring ones ( Fig. 1(c), upper panel).…”
Section: Discussionmentioning
confidence: 93%
“…For example, Belchova et al [39] has found that the suspension of fine powdered synthetic diamonds in acetonitrile can be used as an effective MALDI matrix which allows very sensitive detection of deoxynivalenol (DON). However, it should be mentioned here that if the laser energy used in MALDI-MS is too high, the singly charged carbon clusters of C n + from ND itself can also be observed in the mass spectra [41]. …”
Section: Other Ms Studymentioning
confidence: 99%
“…Interestingly, Maruyama observed even-numbered negative cluster ions of C 120 -C 160 by the laser ablation of a Ni -Co graphite disk while pure graphite never generates anion with such large sizes, showing that the metal atoms or clusters can strongly enhance the formation of large caged cluster anions [30]. Houska et al have found weak signals of negatively charged cluster ions up to C 200 or more in the laser desorption ionization process of nanodiamonds [29]. The largest carbon cluster anions previously observed may belong to the work of Jeon and coworkers [31].…”
Section: Introductionmentioning
confidence: 99%
“…Carbon cluster cations of different sizes and different generation methods or sources have been widely studied [25][26][27][28][29][30][31][32][33][34][35]. Giant carbon clusters as large as C þ 8000 have been observed [29].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation